A Primer on Phased Array Radar Technology for the Atmospheric Sciences - Palmer, Robert; Bodine, David; Kollias, Pavlos; Schvartzman, David; Zrnić, Dusan; Kirstetter, Pierre; Zhang, Guifu; Yu, Tian-You; Kumjian, Matthew; Cheong, Boonleng; Collis, Scott; Frasier, Stephen; et al. (Bulletin of the American Meteorological Society, 2022)
The scientific community has expressed interest in the potential of phased array radars (PARs) to observe the atmosphere with finer spatial and temporal scales. Although convergence has occurred between the meteorological and engineering communities, the need exists to increase access of PAR to meteorologists. Here, we facilitate these interdisciplinary efforts in the field of ground-based PARs for atmospheric studies. We cover high-level technical concepts and terminology for PARs as applied to studies of the atmosphere. A historical perspective is provided as context along with an overview of PAR system architectures, technical challenges, and opportunities. Envisioned scan strategies are summarized because they are distinct from traditional mechanically scanned radars and are the most advantageous for high-resolution studies of the atmosphere. Open access to PAR data is emphasized as a mechanism to educate the future generation of atmospheric scientists. Finally, a vision for the future of operational networks, research facilities, and expansion into complementary radar wavelengths is provided.